Carbonic anhydrase inhibitors: a review on the progress of patent literature (2011–2016). (2nd August 2016) - Lomelino, Carrie; McKenna, Robert
ABSTRACT: Introduction : A large area of carbonic anhydrase (CA) research focuses on the inhibition of human CA IX and CA XII, as these isoforms have been designated as biomarkers and therapeutic targets for various cancer types. Areas covered : Recently, the majority of CA inhibitor (CAI) patents cover compound design, synthesis, and delivery methods for the treatment of glaucoma and cancer. The analysis of included patents highlights the need for isoform specific inhibitors. This review covers the patents of medically relevant carbonic anhydrase inhibitors between 2011–2016. Expert opinion : The improvement of structure-based drug design methods and access to the crystal structures of human CA isoforms have improved inhibitor development. This progress can be observed in relation to the selective inhibition of CA IX for cancer treatments, with one inhibitor in clinical trials. However, the design of nonclassical CAIs is essential to further improve isoform specificity and prevent sulfur allergies.